The Ophiolite Belts and Suture Traces in Pakistan - Shah, S.H.A. (Journal of Himalayan Earth Sciences, 1984)
The paper deals with the four ophiolite belts as indicated by the occurrences of ultramafic rocks, pillow lavas, greenschists, pyroclasts and basaltic flows. Of these four belts, three are indicative of suture zones while one is related with a deep fracture through which ultramafic magma along with other types has intruded.